Intersexuality and its discontents: An analysis of Vijayarajamallika’s journey as an intersex person in Mallikavasantham - George, Aleena; Deepa Mary Francis; Veena Selvam (Research Journal in Advanced Humanities, 2025)
In India, the intersex community, clinically known as persons with disorder of sex development (DSD), persist to be one of the marginalised and stigmatised sexual minority, despite the attempts to achieve queer liberation. Due to their non-conforming sexual and gender identity, they are usually labeled as abnormal, and this often results in them undergoing medical interventions before they reach the age of consent. Vijayarajamallika, a transgender poet from Kerala, is such an intersex person who was subjected to hormone therapy without her informed consent, at a very young age. This paper explores the socio-cultural perspectives which stigmatises intersexuality in India, through an analysis of Vijayarajamallika’s autobiography, Mallikavasantham (2019). It brings forth how the binary construction of sex and gender, and the reluctance to accept sex as a spectrum, alienates and marginalises them. The study also traces how the medical procedures Mallika underwent led to her loss of agency and bodily autonomy, and how this eventually deteriorated her mental and physical health and resulted in psychological issues. It sheds light on the importance of accepting intersex embodiment in its plurality and concludes that only the adoption of an   agency-based model of intersex could support them to achieve liberation. The significance of this paper lies in the absence of a comprehensive literary study in the mentioned area, especially in the cultural landscape of India.